Intramuscular orbital schwannoma: case report and review of the literature - Alotaibi, Hammam A.; Madani, Firas; Althaqib, Rawan N.; AlSulaiman, Hamad M. (Frontiers in Ophthalmology, 2025)
Orbital schwannomas are benign tumors that arise from Schwann cells in the peripheral nerves in the orbit. They typically present after the second decade of life given their slow growth and rarely before then. Diagnosis is based on clinical course and specific imaging modalities; however, the definitive diagnosis is by lesion biopsy. Surgical removal is typically curative. Herein we present the case of an 8-year-old boy with proptosis and diplopia where he exhibited the clinical findings of an orbital mass, however, the characteristic picture of orbital schwannoma was observed on imaging yet found within the inferior rectus muscle, a rare finding indeed.